Understanding The B-Cyclodextrin Inclusion Complex Formation And Its Application In Antimicrobial Active Packaging System - Maniam, Manivannan Melvin Ravindran (Universiti Sains Malaysia, 2020)
~-Cyclodextrin (~-CD) is a 7-glucoses subunit macrocyclic compound that can entrap a guest molecule(s). ~-CD has many potentials in various field including active packaging. One of the important criteria to produce an efficient active packaging system is to have a continuous controlled release of food additives such as antimicrobial agent to help maintaining the quality of food product.